The Effect of Data Protection Regulations in the UU ITE on the Collection and Use of Tax Data - Muh. Akbar Fhad Syahril; Wiwin Wiwin (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2024)
This study examines the influence of data protection regulations in the UU ITE on the collection and use of tax data in Indonesia. The provisions for personal data protection regulated in the IUU ITE, such as the obligation to obtain taxpayer approval and ensure data security, have a significant impact on the process of collecting and managing tax data. Despite the challenges of implementation, strong data protection can increase taxpayer trust and compliance, thereby optimizing state revenue. The study suggests steps that tax authorities can take to collect data effectively while still protecting individual privacy